Thoracic segmental spinal anaesthesia vs general anaesthesia for laparoscopic cholecystectomy: a comparative study - Mahasivabhattu, Sai Srivani; Chembeti Gopalakrishnaiah; P. Sophia; A. Vishnu Vardhan (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Regional anaesthesia techniques are now being preferred over General anaesthesia in patients with major medical problems and those at high risk for GA. Thoracic segmental spinal anaesthesia has recently gained popularity because of its safety and efficacy in procedures like laparoscopic cholecystectomy, breast surgeries etc. Methods: A comparative study involving 50 patients of ASA grade I & II of both genders with age group of 25-55 years, weighing between 50-85 kg posted for lap. Cholecystectomy in GGH, Kakinada for a study period of 5 months. 50 Patients were divided into Group A & Group B with 25 patients in each group. After taking informed & written conscent, Group A patients were given Thoracic Segmental Spinal Anaesthesia at T10 level with Inj.0.5% isobaric Levo-bupivacaine 1.75 ml (13.75 mg) with Inj. Fentanyl 0.25 ml (25 mcg) and Group B patients were given GA with fentanyl, propofol, sevoflurane, succinylcholine and vecuronium. Results: conscious patients with less hemodynamic variability, greater duration of post operative analgesia, greater duration for first rescue analgesia were observed in Group A. Whereas greater hemodynamic variability, intubation response, more requirement of intraoperative opioid, less duration of post operative analgesia, lesser time for first rescue analgesia were observed in Group B. Conclusions: TSSA is safe alternative as it provides excellent analgesia. With TSSA, GA can be avoided in patents with comorbidities.